Alpinia austrosinense (Zingiberaceae), a new combination from China and its relationship with A. pumila - Zou, Pu; Ye, Yu-Shi; Liao, Jing-Ping (Phytotaxa, 2016)
Amomum austrosinense was published in 1982, but examination the morphology of living plants and the type specimens makes it clear that it is a species of Alpinia. Its inflorescence has an involucre of sterile bracts in contrast to absent in Amomum Roxburgh, and the anther crest absent rather than usually present with variously lobed in Amomum. Furthermore, the staminodes are big and not small as in Amomum. Morphological comparisons show that it is very close to Alpinia pumila, from which it can be distinguished by the more densely flowered inflorescence and narrowly elliptic or oblong lamina without whitish stripes between the nerves. Hence the new combination Alpinia austrosinense is proposed.